Identification of heterochromatic variations in nonsyndromic cleft lip and palate - Soumya Raj; Leyon Varghese; Puthucode Viswanathan Narayanan; Suresh Kumar Raveendran; Pulikkottil Raphael Varghese; Alex George (Wolters Kluwer Medknow Publications, 2023)
Introduction: Orofacial cleft (OFC) has been one of the major common congenital anomalies exhibiting prominent ramifications allied with the medical, social, psychological, and economic strands. Most OFC occurrences do not have additional features, so they are categorized as nonsyndromic. The classification of the aforesaid complication has been directed toward the following categories: cleft lip (CL) with cleft palate, isolated CL, and finally the isolated cleft palate. The recent research concerning the aforementioned anomalies always searches for advanced novel inferences linked with the chromosomal perspectives since some of the specific genes are probably known to produce significant effects over the anomalies. Materials and Methods: Karyotyping was performed for all 130 cases of nonsyndromic cleft lip and palate (NSCLP). Aseptic collection of peripheral blood lymphocyte culture (PBLC) was performed from the patients using heparin vacutainers, and C-banding was done to confirm heterochromatic variations. Results: A total of 130 patients known to have the NSCLP were recruited for this study of which 88 cases (68%) had CL along with cleft palate, 18 cases (14%) had isolated CL and 24 cases (18%) had isolated cleft palate. Cytogenetic analysis by G-banding by Trypsin and Giemsa (GTG) banding in these patients revealed five cases (3.84%) with abnormal karyotype where a higher frequency of pericentric inversion in the analyzed region, specifically the chromosome 9, inv(9)(p11p13) was observed. Conclusion: The heteromorphisms or structural rearrangements involving the centromere were confirmed by centromere banding in two cases. Understanding the etiology with special inference on the above-said perspectives is significant to develop an effective strategy for the prevention and treatment of the individuals affected with the anomalies.